1997
DOI: 10.1002/(sici)1520-6408(1997)21:3<223::aid-dvg5>3.3.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of a heat shock cognate cDNA of zebrafish, hsc70, and developmental expression of the corresponding transcripts

Abstract: To elucidate the potential role of the hsp70 gene family in developmental processes in vertebrates, we chose to study the expression of one of these genes in zebrafish. A zebrafish gastrula cDNA library was screened with a Pleurodeles waltl hsp70 cDNA probe. A 2.3-kb cDNA was thus isolated and sequenced. The predicted amino acid sequence contained an open reading frame encoding for a 649-amino acid polypeptide. Sequence analysis showed strong homology with hsp70-related gene sequences in other species; in part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 0 publications
1
22
0
Order By: Relevance
“…Mar-HSC70 mRNA was particularly enriched in the ovary of prawns. Similar enriched patterns of HSC70 transcripts have been reported in zebrafish and Drosophila during embryogenesis (Perkins et al 1990;Santacruz et al 1997). Therefore, the tissue-specific enrichment of Mar-HSC70 transcripts in prawns may signify a critical role for this stress protein during reproductive events.…”
Section: Discussionsupporting
confidence: 72%
“…Mar-HSC70 mRNA was particularly enriched in the ovary of prawns. Similar enriched patterns of HSC70 transcripts have been reported in zebrafish and Drosophila during embryogenesis (Perkins et al 1990;Santacruz et al 1997). Therefore, the tissue-specific enrichment of Mar-HSC70 transcripts in prawns may signify a critical role for this stress protein during reproductive events.…”
Section: Discussionsupporting
confidence: 72%
“…Zebrafish hsc70 is expressed as a maternal protein, and mRNA in the fertilized eggs and its zygotic gene expression occur after gastrulation, especially in the brain and yolk sac (Graser et al 1996;Santacruz et al 1997). When segmentation starts, hsc70 is expressed in the dorsal trunk neural tube, the lateral plate mesoderm, and the tail bud.…”
Section: -1 Control Of Tgf-β β β β β Receptor Activationmentioning
confidence: 99%
“…These studies and others revealed that the use of hsp as an indicator of stressed states in fish is a very complex issue. The hsp response can vary according to tissue (Rabergh et al, 2000;Smith et al, 1999), distinct hsp families (Smith et al, 1999) and stressor (Airaksinen et al, 2003), and the sensitivity of hsp expression can also vary with the species (Basu et al, 2001;Nakano and Iwama, 2002), developmental stage (Santacruz et al, 1997;Lele et al, 1997;Martin et al, 2001) and season (Fader et al, 1994).…”
Section: Heat Shock Proteins As Indicators Of Stressmentioning
confidence: 99%